RETRACTED: Characteristic of Kalmyk servicing bulls of different genotypes - Chimidova Nadezhda; Moiseikina Ludmila; Ubushieva Victoria; Ubushieva Altana; Khakhlinov Arslang; Radchikov Vasiliy (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001